A Contemporary Reading of the Amorous Subject in Lyrical Tradition: Cavalcanti and Rudel Intertexted in Petrarch - Lahiri, Sharmistha (Spunti e Ricerche, 2016)
The essay explores the intertextual links that connect Petrarch's lyrics of love with the poetry of interiority of Guido Cavalcanti in trying to understand some of the founding concepts and uses which informed the lyrical tradition, and traces their beginnings in romance poetry. While the areas of intersection between Cavalcanti and Petrarch are probed through the readings of a selection of lyrics from Cavalcanti's Rime and Petrarch's Rerum …, a consideration of the troubadours' poetry and its engagement with the trope of distance, for example, in the canso of Jaufré Rudel, provides useful sources from which some of the key themes and motifs of the lyrical tradition can be gleaned. To this end, Roland Barthes's A Lover's discourse: Fragments provides an interesting model for the analysis of the discourse of the amorous subject. As Barthes shows, distance plays a crucial role in creating the space of yearning and absence is an essential figure in this discourse. In the lyrical tradition, a narrative is thus formed in which, as Calvino would have said, Jaufré Rudel creates voyage as the form to which Cavalcanti adds fragmentation as the concept and Petrarch develops introspection as its language.